Study of the Different Transmission Line Faults for a Grid Connected Wind Farm with Different Types of Control Method for RSC - Reza Najafi (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
Wind power stations, many  located in remote areas; so they are characterized by weak grids and are often submitted to power system disturbance like faults. In this paper, the behaviour of a wind energy conversion system that uses the control of the rotor side converter (RSC) by three different methods  under faulty conditions is presented. The behaviour of these systems during a grid failure is an important issue.  DFIG is analysed and simulated under differing faulty conditions in the environment of MATLAB/SIMULINK. Simulation results show that the proposed method has proper operation during fault conditions.